The Political Economy of High-Stakes Whistleblowing in South Africa - Radulovic, Ugljesa (NBP. Nauka, bezbednosti, policija, 2025)
Whistleblowing, which is when organizational insiders expose wrongdoing to an authority that can effect action, has been established as a mechanism that possesses the capacity to combat, or event prevent, high-level malfeasance. Much global research has explored the frequency and the nature of retaliation that whistleblowers are subjected to. However, there is a dearth of research regarding the political economy of whistleblowing. This paper, employing documents as sources of data, has sought to explore the global pattern of fallout experienced by whistleblowers, with the experiences of South African whistleblowers being testament to this. Thus, the cases of South African high-stakes whistleblowing are given particular attention. This paper asserts that weak whistleblower protection legislation is a large contributor as to why whistleblowers face frequent and severe reprisals in South Africa. It also determines that there is an absolute power imbalance between those who report wrongdoing and those who perpetuate it. Ultimately, this paper’s unique contribution lies in establishing that the issue of weak legislation is compounded by the neoliberal political economy. With South Africa exemplifying the neoliberal political economy, initiatives aimed at addressing issues of corruption (such as reinforcing whistleblower protection laws) become difficult in a system where criminal and fraudulent capital is rife, and a wide spectrum of corrupt and socially pernicious practices are common. This paper does, however, concede that pro-social practices can exist within such a system, with the actions of whistleblowers being evidence of this. However, revising the whistleblower protection instrument would require cultural and political-economic resistance to neoliberalism.